In vitro antioxidant and antibacterial potential of Moringa oleifera Lam - Abdulaziz Rabiu Abdulkadir
The antioxidant and antimicrobial products from plant source, which are safer is not sufficient in the markets. This study was aimed to assess antioxidant activity, estimate total phenolic, total flavonoid, proximate contents and antibacterial potential from different parts of Moringa oleifera crude extract. DPPH radical scavenging and Ferric-reducing antioxidant power (FRAP) assay were applied to evaluate antioxidant activity. Antibacterial potential of the samples were tested against four different bacterial strains which is S. aureus, E. coli, P. aeruginosa and B. cereus by the used of agar well diffusion method. However, estimation of total phenolic, flavonoid and proximate content were also done. Methanolic extract of bark, leaf, flower, and stem showed high free radical scavenging activity with ICso-value of 40, 320, 425 and 720 (ug/ml) respectively. FRAP assay also show the same pattern with bark having highest value 1499.67 ± 49.98 J.lMFe . (II)/g, and the lowest was in seed extract 126.67 ± 4.19 J.lMFe (II)/g. Methanolic pod and seed extract showed low activity, with (195.00 ± 0.82) and (126.67 ± 4.19) (J.lMFe (II)/g), respectively. The highest phenolic content was observed in methanolic of bark (55.84 ± 2.92), flower (48.04 ± 2.45), leaf (45.9 ± 1.17) and pod (44.89 ± 4.82) (mg GAE/g), respectively. The total flavonoid content of leaf extract was found to 98.67 ± 2.10 mg QAE/g. Proximate content was higher in pods, leaf, seed and stem for moisture (8.10 ± 0.004%), ash (9.28 ± 0.135%), crude protein (26.57 ± 1.602%) and crude fibre (44.27 ± 0.722%), respectively. Where crude fat and carbohydrate were highed in seed and stem with bark having (20.12 ± 0.058%) and (31.12%). Bark, stem with bark where most susceptible against gram positive, bark extract revealed inhibition zone of(14.0 ± 0.50 mm) and (10.67 ± l.37 mm) for S. aureus and B. cereus respectively. Wherere stem with bark showed inhibition zone of (13.5 ± 1.50 mm) and (10.0 ± 0.50 mm) from S. aureus and B. cereus respectively. While leaf was found to be susceptible against both of gram positive and gram negative bacteria, having zone of inhibition (12.0 ± 0.50 mm) and (10.0 ± 1.00 mm) from S. aureus and E. coli respectively. This may be related to the high flavonoid content of the leaf (98.67 ± 0.54 mg QAE/g). This study showed that Moringa oleifera might be a good source of natural antioxidant compounds and nutritional component. Therefore Moringa oleifera can be utilised to cure oxidative related problems, antimicrobial diseases and also as a good supplement to human diet which to be elucidated in future research.